Short periods of instruction improve learners' phonological categories for L2 suprasegmental features. (June 2019) - McAndrews, Mark
Abstract: Second language listening scholars have advocated for greater instructional emphasis on discrete listening sub-skills, including the ability to perceive suprasegmental features and integrate them into listening comprehension. The goals of the current study were to review research that investigated the effects of instruction on suprasegmental listening skills, and determine the extent to which instruction is effective in improving those skills. A comprehensive search identified 17 relevant primary studies that investigated a range of target languages and suprasegmental features. Effects of instruction were then aggregated across studies. The results of the meta-analysis indicate that instruction has a large, positive effect on the ability of learners to develop phonological categories for suprasegmental features in the target language ( d  = .94). Further, these effects were observed after periods of instruction that lasted only a few hours. Based on these findings, it is recommended that teachers provide suprasegmental training opportunities for learners. Future research should investigate the effect of instruction beyond the level of phonological categories, focusing on learners' skill in integrating suprasegmental features into listening comprehension.